Biografi dan Bibliografi Ahmad Khatib Al-Mingkabawi: Inspirasi Tentang Ilmuwan Era Revolusi Industri 4.0 - Radinal Mukhtar Harahap; Ahmad Fauzi Ilyas; Irwan Haryono (Universitas Islam Negeri Sumatera Utara, 2020)
This article is based on the discursion that Amin Abdullah discussed as the Third Generation of Disrupsi Era Higher Education. He mentioned that the era termed also as Industrial Revolution 4.0 will demand a new way of thinking and management of higher education governance so as to be able to compete in the recruitment of teachers, researchers, and professors superior in the world. Therefore, in the scientific sphere he mentions that paradigms, which are not only monodisciplinary, even multi-, inter- and transdisciplinary are urgently needed. The problem is the absence or absence of inspiration about the figure who can do that, when, inevitably, it must be lived. Through library research, this paper seeks to bring about ahmad khatib biography and bibliography, which is expected to be an inspiration or reflection of a scientist's personality. Despite living in the late 19th and early 20th centuries, his thinking continues to be reviewed to this day. The results of the study found that Ulama Nusantara from West Sumatra was very competent to see the phenomenon of society as he was then adept at providing solutions in writing, which at the same time accommodated several scientific disciplines even in contact with other experts. It was also found that his self-image was recognized in a global and international context, although it did not dispel his deep concerns on his own country's issues.